Peran Implementasi Picture Archiving and Communication System dalam Pelayanan Radiologi di Rumah Sakit Premier Bintaro - P V L Suandari; I Putu Eka Juliantara; Erni R Rusmana (Jurnal Manajemen Kesehatan Indonesia, 2020)
Premier Bintaro Hospital is equipped with High-end modalities with various types of advanced radiological examinations. There are several service centers that require continuous imaging support, such as vascular centers, Pain Centers, Spine centers and others. Integrated storage and access to patient data is needed to improve work efficiency. With the implementation of Picture Archiving And Communication System (PACS) in Radiology Unit, there are improvements in services and increased productivity when compared to previous system. This research will discuss a number of issues related to the role of PACS in Radiology services as evaluation material for services compared with the system before PACS is implemented. This research was made to determine the role of PACS in Premier Bintaro Hospital. This research is prepared with literature review, observation, and documentation. The application of PACS in Premier bintaro Hospital basically has the same workflow compared to workflows in general. Application of HL7 interface System which is equipped with DMWL makes PACS applied will integrated properly with HIS / RIS. The advantages of implementing PACS are more on data integration, storage, data editing, and presentation of data in digital form. The lack of PACS is more focused on the stability of the connection as the basis of the data transportation path needed. The challenge faced in the future is the problem of strengthening the stability of connection and education to users related.